Tariff liberalization in the RCEP trade agreement and impact on India's automobile industry: An applied general equilibrium analysis - Badri G. Narayanan; Rahul Sen; Sadhana Srivastava (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2019)
Although India has been experiencing a significant trade deficit with respect to RCEP members, and therefore likely to be extremely cautious in terms of committing to any tariff liberalization under a formal RCEP agreement. This is mainly due to the fear that cheaper imports through RCEP will be bad for India's domestic import competing producers and generate job losses, although preferential market access in RCEP countries would be also providing an opportunity for Indian exporters to plug into trade in GVC goods. Therefore, it makes sense to analyse tariff liberalization at a sub-sectoral level, which seems to be more amenable to trade in GVC goods. Surprisingly, adequate attention has not been paid by researchers towards general equilibrium effects of trade liberalization particularly involving trade in global value chains (GVC) goods, in spite of its emergence being an established phenomenon among RCEP members including India. This paper breaks new ground by undertaking a Computable General Equilibrium (CGE) simulation that utilizes 2015 baseline data in an updated GTAP 9 database to study the automobile sector of trade in GVC goods in the Indian context. The key here is to analyze the welfare effects for India, in a probable futuristic scenario of a full tariff liberalization (with and without any productivity improvement) as part of the ongoing RCEP negotiations, and the specific impact of this on output, prices and trade in the automobile and auto-parts industry, wherein GVC led trade assumes significance. Specifically, we split the automobiles sector into both parts and components of automobiles, as well as the final assembly, hitherto not attempted in the existing literature. Two policy simulations are conducted, the first involving a full tariff liberalization within RCEP members, while the second scenario adds a sector-specific endogenous productivity shock to it. Our results suggest that there is a positive overall welfare impact due to RCEP on the Indian economy, and trade balance improves. However, the automobiles and auto-parts industry in India will specifically witness an adverse impact, unless an annual productivity growth of at least 2.5% is achieved. The paper therefore suggests that from the perspective of India, it is vitally important to focus on improving domestic productivity in the manufacturing sector, while considering any future RTAs, including RCEP, that negotiates a phased tariff liberalization.
Keywords: F15; F61; O53; 330; India; RCEP; trade in GVC goods; GTAP model; automobiles; auto-parts; productivity